KOMPETISI ALAT PENANGKAPAN IKAN SKALA KECIL DI PELABUHAN PERIKANAN PANTAI TEGALSARI - Lukman Hakim; Eko Sri Wiyono; Ronny Irawan Wahju (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2018)
The fishermen in Tegalsari Fishing Port have been using vary of fishing gears that is feared could competing in getting catches. This research aims to identify fishing gear types according to fishing gear vessel’s volume, fishing time and frequency in every operation, fishing gears productivity, and fishing gears competition. The subject of this research are four biggest number of fishing gear units in PPP Tegalsari (cantrang, arad, gillnet, and mini purse seine) with fishing vessel volume below 10 GT. Samples were taken with purposive sampling method  and collected through filling out the questionnaires. The fishing gears’s productivity determined by the number of catch per unit effort (CPUE). Furthermore, the  fishing gear competition mapped by classified the matrix of transformed fishing gear’s productivity number into some clusters with hierarchycal cluster analysis (HCA). The results show the dominant fishing gear that local fishermen use are cantrang (5, 6, 10 GT), arad (3, 5, 6, 10 GT), gillnet (6 GT), and mini purse seine (9 GT), the highest average of fishing gear operation time is gillnet (3 hours), and the least is mini purse seine (± 1 hour) and the highest average of fishing setting number is cantrang by 27 times/trip and mini purse seine is the least by 5 times/trip, the highest productivity gained by cantrang (5163 kg/trip) and the least is Gillnet (363 kg/trip), and the most intensive fishing gear competition is between cantrang (5 and 6 GT), arad (3,5, and 6 GT), and gillnet (3 GT).Keywords: Competition, fishing gear, productivityABSTRAKNelayan di Pelabuhan Perikanan Pantai Tegalsari menggunakan alat tangkap yang beragam. Dikhawatirkan antar alat tangkap saling berkompetisi dalam mendapatkan hasil tangkapan ikan. Penelitian ini bertujuan untuk mengidentifikasi jenis  alat  tangkap  berdasarkan  GT kapal, waktu untuk 1 kali  operasi dan frekuensinya dalam satu trip penangkapan ikan, produktivitas  alat  tangkap, dan kompetisi antar alat tangkap. Alat tangkap yang diamati adalah cantrang, arad, gillnet dan mini purse seine yang dioperasikan menggunakan kapal berukuran ≤ 10 GT. Pengumpulan data dilakukan melalui penyebaran kuesioner. Produktivitas alat tangkap ditentukan berdasarkan nilai CPUE dan kompetisi antar alat tangkap ditentukan menggunakan metode hierachycal cluster analysis. Hasil penelitian menunjukkan: jenis alat tangkap berdasarkan  GT  kapal yakni  cantrang  (5, 6 dan 10 GT), arad (3,  5,  6 dan 10 GT),  gillnet (6 GT), dan mini purse seine (9 GT); waktu untuk 1 kali operasi penangkapan ikan  tertinggi  pada alat  tangkap gillnet (3 jam)  dan  terendah  pada  cantrang dan  mini purse seine (± 1 jam) serta jumlah operasi penangkapan ikan per trip tertinggi pada alat tangkap cantrang (27 kali/trip) dan terendah pada mini purse seine (5 kali/trip); produktivitas tertinggi pada alat tangkap cantrang (5163 kg/trip) dan terendah pada gillnet (363 kg/trip); dan antar alat tangkap yang berkompetisi secara ketat adalah cantrang (5 dan 6 GT), arad (3, 5 dan 6 GT), dan gillnet 6 GT.Kata kunci: Kompetisi, alat penangkapan ikan, produktivitas.